THEORETICAL BASIS FOR STUDYING INFORMATIVITY IN MEDIA LINGUISTICS AND COMMUNICATIVE STYLISTICS OF THE ENGLISH LANGUAGE (Zamonaviy dunyoda pedagogika va psixologiya, 2022)
Discursive ontology: Ontology is a section of humanitarian knowledge, in which questions of existence are considered as a single system of being of nature and the social and spiritual world of man. Unity implies the possibility of discretization of integrity and the allocation of separate layers of reality for scientific understanding.